Knock at the cabin [videorecording (DVD)] - Shyamalan, M. Night; Desmond, Steve; Sherman, Michael (Screenwriter); Bautista, David, 1969-; Groff, Jonathan; Aldridge, Ben; Amuka-Bird, Nikki, 1976-; Cui, Kristen; Quinn, Abby; Grint, Rupert, 1988-; Tremblay, Paul (Universal Studios, 2023)
While on vacation, a girl and her parents are taken hostage by armed strangers who demand that the family make a choice to prevent the apocalypse.